Phylogenomic analyses reveal introgression and cryptic speciation in the globally distributed, vector-transmitted pathogen Plasmodium relictum - Esther Weyer; Angela N. Theodosopoulos; Vaidas Palinauskas; Staffan Bensch; Helena Westerdahl; Mélanie Duc; Arif Ciloglu; Xi Huang; Kyeong Soon Kim; Yoshio Tsuda; Carter T. Atkinson; Pavel Zehtindjiev; et al. (Molecular Phylogenetics and Evolution, 2026)

Acoustic Monitoring Enables Multi‐Taxa Conservation Assessment and Prioritisation Over Large Scales and for Rare and Cryptic Species - Adham Ashton‐Butt; Stuart E. Newson; Jeffrey W. Doser; Simon Gillings; Tatiana Kornienko; Viktar Fenchuk; James W. Pearce‐Higgins; Chris Scott; Philip W. Atkinson (Global Ecology and Biogeography, 2025)
Aim To combat the global biodiversity crisis, robust and scalable data are needed to target, monitor and evaluate conservation efforts, particularly in data‐poor regions and for cryptic taxa. Passive acoustic monitoring (PAM) has the potential to provide solutions, but real‐world examples are still rare. We demonstrate how PAM data can be used to rapidly and effectively map distributions of multiple taxa over large scales, in data‐poor regions. We show how these data can be used to assess the importance of existing protected areas and prioritise future conservation efforts, including for rare and cryptic species often neglected in such assessments. Location Global with a case study from Polesia, Eastern Europe. Time Period Present. Major Taxa Studied Bats, Birds, Small mammals and Bush crickets. Methods Using machine‐learning and manual verification, we identified bats, nocturnally active birds, small mammals and bush crickets from over 34,000 monitoring hours at 506 sites in the Polesia region of Belarus and Ukraine. Using multi‐species generalised mixed models in a Bayesian framework, we then predicted occupancy and acoustic activity for these species and their associations with protected areas, over a 151,000 km 2 project area. We identified areas of high conservation priority as measured by species richness and/or importance for globally or regionally threatened species. Main Conclusions Our approach provides a roadmap for collecting and processing large‐scale, multi‐taxa biodiversity data using passive acoustic monitoring. In our case study region, we show that although existing protected areas contain a relatively large proportion of high conservation priority areas, there are significant gaps in the protected area network. We also show low surrogacy of areas of high conservation priority between taxa at fine scales, but did at larger scales, showing the importance of multi‐taxa monitoring to prioritise protected areas that conserve a wide variety of species.

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Chronically elevated depressive symptoms interact with acute increases in inflammation to predict worse neurocognition among people with HIV - Rowan Saloner; Emily W. Paolillo; Robert K. Heaton; David J. Grelotti; Murray B. Stein; Andrew H. Miller; J. Hampton Atkinson; Scott L. Letendre; Ronald J. Ellis; Igor Grant; Jennifer E. Iudicello; David J. Moore (Journal of NeuroVirology, 2021)

Use of surrogate species to cost‐effectively prioritize conservation actions - Michelle Ward; Jonathan R. Rhodes; James E.M. Watson; James Lefevre; Scott Atkinson; Hugh P. Possingham (Conservation Biology, 2020)
Conservation efforts often focus on umbrella species whose distributions overlap with many other flora and fauna. However, because biodiversity is affected by different threats that are spatially variable, focusing only on the geographic range overlap of species may not be sufficient in allocating the necessary actions needed to efficiently abate threats. We developed a problem‐based method for prioritizing conservation actions for umbrella species that maximizes the total number of flora and fauna benefiting from management while considering threats, actions, and costs. We tested our new method by assessing the performance of the Australian federal government's umbrella prioritization list, which identifies 73 umbrella species as priorities for conservation attention. Our results show that the federal government priority list benefits only 6% of all Australia's threatened terrestrial species. This could be increased to benefit nearly half (or 46%) of all threatened terrestrial species for the same budget of AU$550 million/year if more suitable umbrella species were chosen. This results in a 7‐fold increase in management efficiency. We believe nations around the world can markedly improve the selection of prioritized umbrella species for conservation action with this transparent, quantitative, and objective prioritization approach.

Renewable energy development threatens many globally important biodiversity areas - Jose A. Rehbein; James E. M. Watson; Joe L. Lane; Laura J. Sonter; Oscar Venter; Scott C. Atkinson; James R. Allan (Global Change Biology, 2020)
Transitioning from fossil fuels to renewable energy is fundamental for halting anthropogenic climate change. However, renewable energy facilities can be land‐use intensive and impact conservation areas, and little attention has been given to whether the aggregated effect of energy transitions poses a substantial threat to global biodiversity. Here, we assess the extent of current and likely future renewable energy infrastructure associated with onshore wind, hydropower and solar photovoltaic generation, within three important conservation areas: protected areas (PAs), Key Biodiversity Areas (KBAs) and Earth's remaining wilderness. We identified 2,206 fully operational renewable energy facilities within the boundaries of these conservation areas, with another 922 facilities under development. Combined, these facilities span and are degrading 886 PAs, 749 KBAs and 40 distinct wilderness areas. Two trends are particularly concerning. First, while the majority of historical overlap occurs in Western Europe, the renewable electricity facilities under development increasingly overlap with conservation areas in Southeast Asia, a globally important region for biodiversity. Second, this next wave of renewable energy infrastructure represents a ~30% increase in the number of PAs and KBAs impacted and could increase the number of compromised wilderness areas by ~60%. If the world continues to rapidly transition towards renewable energy these areas will face increasing pressure to allow infrastructure expansion. Coordinated planning of renewable energy expansion and biodiversity conservation is essential to avoid conflicts that compromise their respective objectives.

Modelling the distribution of hard seabed using calibrated multibeam acoustic backscatter data in a tropical, macrotidal embayment: Darwin Harbour, Australia - P. Justy W. Siwabessy; Maggie Tran; Kim Picard; Brendan P. Brooke; Zhi Huang; Neil Smit; David K. Williams; William A. Nicholas; Scott L. Nichol; Ian Atkinson (Marine Geophysical Research, 2018)

The Local Early Action Planning (LEAP) Tool: Enhancing Community-Based Planning for a Changing Climate - Supin Wongbusarakum; Meghan Gombos; Britt-Anne A. Parker; Catherine A. Courtney; Scott Atkinson; Willy Kostka (Coastal Management, 2015)

Status and Priority Capacity Needs for Local Compliance and Community-Supported Enforcement of Marine Resource Rules and Regulations in the Coral Triangle Region - Robert Pomeroy; John Parks; Kathleen Reaugh-Flower; Mar Guidote; Hugh Govan; Scott Atkinson (Coastal Management, 2015)

Developing Marine Protected Area Networks in the Coral Triangle: Good Practices for Expanding the Coral Triangle Marine Protected Area System - Rebecca Weeks; Porfirio M. Aliño; Scott Atkinson; Pacifico Beldia; Augustine Binson; Wilfredo L. Campos; Rili Djohani; Alison L. Green; Richard Hamilton; Vera Horigue; Robecca Jumin; Kay Kalim; et al. (Coastal Management, 2014)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Neurocognitive functioning in acute or early HIV infection - David J. Moore; Scott L. Letendre; Sheldon Morris; Anya Umlauf; Reena Deutsch; Davey M. Smith; Susan Little; Alexandra Rooney; Donald R. Franklin; Ben Gouaux; Shannon LeBlanc; Debra Rosario; et al. (Journal of NeuroVirology, 2011)

Neurobehavioral effects of human immunodeficiency virus infection among former plasma donors in rural China - Robert K Heaton; Lucette A Cysique; Hua Jin; Chuan Shi; Xin Yu; Scott Letendre; Donald R Franklin; Christopher Ake; Ofilio Vigil; J Hampton Atkinson; Thomas D Marcotte; Igor Grant; et al. (Journal of NeuroVirology, 2008)

Neurocognitive Effects of Methamphetamine: A Critical Review and Meta-analysis - J. Cobb Scott; Steven Paul Woods; Georg E. Matt; Rachel A. Meyer; Robert K. Heaton; J. Hampton Atkinson; Igor Grant (Neuropsychology Review, 2007)

An integrated genetic linkage map of the laboratory rat - Donna M. Brown *, , Tara C. Matise; George Koike; Jason S. Simon; Eric S. Winer; Sarah Zangen; Michael G. McLaughlin; Masahide Shiozawa; O. Scott Atkinson; James R. Hudson, Jr.; Aravinda Chakravarti; Eric S. Lander **, , Howard (Mammalian Genome, 1998)